The pupil near response is short lasting and intact in virtual reality head mounted displays - Pielage, Hidde; Zekveld, Adriana A.; van de Ven, Sjors; Kramer, Sophia E.; Naber, Marnix (Multidisciplinary Digital Publishing Institute, 2023)
The pupil of the eye constricts when moving focus from an object further away to an object closer by. This is called the pupil near response, which typically occurs together with accommodation and vergence responses. When immersed in virtual reality mediated through a head-mounted display, this triad is disrupted by the vergence-accommodation conflict. However, it is not yet clear if the disruption also affects the pupil near response. Two experiments were performed to assess this. The first experiment had participants follow a target that first appeared at a far position and then moved to either a near position (far-to-near; FN) or to another far position (far-to-far; FF). The second experiment had participants follow a target that jumped between five positions, which was repeated at several distances. Experiment 1 showed a greater pupil constriction amplitude for FN trials, compared to FF trials, suggesting that the pupil near response is intact in head-mounted display mediated virtual reality.
Keywords: eye tracking; gaze; head-mounted display; pupil near response; Pupillometry; vergence; vergence-accommodation conflict; virtual reality; Ophthalmology; Sensory Systems